USE OF INTERACTIVE METHODS TO DEVELOP STUDENTS' SOCIO-CULTURAL COMPETENCE THROUGH MULTIMEDIA DEVICES (Journal of Universal Science Research, 2023)
The article deals with the issue of the usage of multimedia devices in developing socio-cultural competence of students. The article describes the creation of e-books and its requirements of implementing in teaching foreign language process. Particularly, harmonious implementation of electronic textbooks in full traditional lessons in the context of independent learning results in intensified learning. As a result, today there is an opportunity for every pedagogue to introduce modern pedagogical technologies into the teaching process. The use of various interactive methods can lead students to become active participants in the learning process.